Synchronous triple colorectal carcinoma: a case report and review of literature - Cheng, Ji (Int J Clin Exp Pathol, 2015)
Synchronous colorectal carcinoma defines as multiple malignant lesions presented in a single patient at initial diagnosis. We report a case of triple synchronous colorectal carcinoma without related familial history. Preoperative computed tomography (CT) scan and endoscopic examination suggested multiple malignant lesions occurred in separate segments of colon. Then we performed laparoscopic total colectomy and ileorectal anastomosis with a J-type pouch. Post operative pathological examination confirmed the malignant characteristics of the triple lesions. The mini review summarizes the clinicopathological and molecular features of synchronous colorectal carcinoma based on current literatures. It appears to probably have significant distinctions with solitary tumors in terms of pathological type, primary locations and microsatellite instability.